(untitled) (Dinamika Ilmu, 2022)
Recognizing the position and validity of science in understanding religion has led to very diverse algorithms in the Islamic world. It must be admitted that before the fourteenth century, there were no views on the confrontation of or separation of the realm of science and religion. Although after the nineteenth century, the advent of modernist discourse in the Islamic world’s cultural, social, and political programs and methods set the grounds for a dialectic path on the connection between religion and science. In this regard, Muslim thinkers have given distinct responses to Western modernization, such as agreeing, rejecting, or transforming this claim according to Islamic attitudes. This article seeks to conduct a theoretical interpretation and investigation of the foundations and arguments of two Muslim thinkers, Syed Muhammad Naquib Al-Attas and Pervez Amirali Hoodbhoy with “functionalism” and “symbolism” approaches to science. These two thinkers have paid special attention to religion, science, and modern technology, while they have different fundamental views on the relationship between science and religion.